DNA methylation and copy number variation analyses of human embryonic stem cell–derived neuroprogenitors after low-dose decabromodiphenyl ether and/or bisphenol A exposure. (May 2018) - Du, L; Sun, W; Li, XM; Li, XY; Liu, W; Chen, D
The polybrominated diphenyl ether flame retardants decabromodiphenyl ether (BDE-209) and bisphenol A (BPA) are environmental contaminants that can cross the placenta and exert toxicity in the developing fetal nervous system. Copy number variants (CNVs) play a role in a number of genetic disorders and may be implicated in BDE-209/BPA teratogenicity. In this study, we found that BDE-209 and/or BPA exposure decreased neural differentiation efficiency of human embryonic stem cells (hESCs), although there was a >90% induction of neuronal progenitor cells (NPCs) from exposed hESCs. However, the mean of CNV numbers in the NPCs with BDE-209 + BPA treatment was significantly higher compared to the other groups, whereas DNA methylation was lower and DNA methyltransferase(DNMT1 and DNMT3A) expression were significantly decreased in all of the BDE-209 and/or BPA treatment groups compared with the control groups. The number of CNVs in chromosomes 3, 4, 11, 22, and X in NPCs with BDE-209 and/or BPA exposure was higher compared to the control group. In addition, CNVs in chromosomes 7, 8, 14, and 16 were stable in hESCs and hESCs-derived NPCs irrespective of BDE-209/BPA exposure, and CNVs in chromosomes 20 q11.21 and 16 p13.11 might be induced by neural differentiation. Thus, BDE-209/BPA exposure emerges as a potential source of CNVs distinct from neural differentiation by itself. BDE-209 and/or BPA exposure may cause genomic instability in cultured stem cells via reduced activity of DNA methyltransferase, suggesting a new mechanism of human embryonic neurodevelopmental toxicity caused by this class of environmental toxins.